New Insights Into the Threshold Values of Multi-Locus Sequence Analysis, Average Nucleotide Identity and Digital DNA–DNA Hybridization in Delineating Streptomyces Species - Hu, Siren; Li, Kaiqin; Zhang, Yifei; Wang, Yinfeng; Fu, Li; Xiao, Yan; Tang, Xinke; Gao, Jian (Frontiers in Microbiology, 2022)
Multi-locus sequence analysis (MLSA) has been proved to be a useful method for Streptomyces identiﬁcation and MLSA distance of 0.007 is considered as the boundary value. However, we found that MLSA distance of 0.007 might be insufficient to act as a threshold according to the correlations among average nucleotide identity based on MuMmer ultra-rapid aligning tool (ANIm), digital DNA–DNA hybridization (dDDH) and MLSA from the 80 pairs of Streptomyces species; in addition, a 70% dDDH value did not correspond to a 95-96% ANIm value but approximately to 96.7% in the genus Streptomyces. Based on our analysis, it was proposed that when the MLSA distance value between a novel Streptomyces and a reference strain was < 0.008, the novel strain could be considered as a heterotypic synonym of the reference strain; when the MLSA distance value was ≥ 0.014, the novel strain could be regarded as a new Streptomyces species; when the MLSA distance value was between 0.008 and 0.014 (not included), the dDDH or ANIm value between a new strain and a reference strain must be calculated in order to determine the taxonomic status of a novel strain. In this context, a 70% dDDH or 96.7% ANIm value could act as the threshold value in delineating Streptomyces species, but if the dDDH or ANIm value was less than but close to 70% or 96.7% cut-off point, the taxonomic status of a novel strain could only be determined by a combination of phenotypic characteristics, chemotaxonomic characteristics and phylogenomic analysis. Keywords: New insights; ANIm; dDDH; MLSA; Streptomyces.